2001
DOI: 10.1096/fj.00-0388com
|View full text |Cite
|
Sign up to set email alerts
|

Dominant cell death induction by extramitochondrially targeted apoptosis‐inducing factor

Abstract: The complete AIF cDNA comprising the amino-terminal mitochondrial localization sequence (MLS) and the oxidoreductase domain has been fused in its carboxyl terminus to enhanced green fluorescent protein (GFP), thereby engineering an AIF-GFP fusion protein that is selectively targeted to the mitochondrial intermembrane space. Upon induction of apoptosis, the AIF-GFP protein translocates together with cytochrome c (Cyt-c) to the extramitochondrial compartment. Microinjection of recombinant AIF leads to the releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
193
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(207 citation statements)
references
References 33 publications
10
193
2
2
Order By: Relevance
“…However, the predominant localization of extra-mitochondrial AIF was the nucleus. This has been extensively documented for human and mouse AIF (Loeffler et al, 2001;Ye et al, 2002;Cande et al, 2002Cande et al, , 2004a, and also applies to the AIF ortholog from yeast (S. cerevisiae). Yeast AIF localized at distinct foci within the nucleus upon induction of apoptosis by chronological aging.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the predominant localization of extra-mitochondrial AIF was the nucleus. This has been extensively documented for human and mouse AIF (Loeffler et al, 2001;Ye et al, 2002;Cande et al, 2002Cande et al, , 2004a, and also applies to the AIF ortholog from yeast (S. cerevisiae). Yeast AIF localized at distinct foci within the nucleus upon induction of apoptosis by chronological aging.…”
Section: Resultsmentioning
confidence: 95%
“…While the biological significance of the AIF-RNA interaction remains a conundrum, AIF binding to DNA has been amply documented in apoptotic cells (Susin et al, 1999Daugas et al, 2000;Cande et al, 2002Cande et al, , 2004aZhu et al, 2003), and it appears clear that AIF can mediate chromatin condensation. Thus, recombinant AIF induces marked pyknosis when added to isolated nuclei or when microinjected into intact cells Loeffler et al, 2001). Moreover, the injection of AIF-neutralizing antibodies or the knockdown of AIF expression with small interfering RNAs has established that endogenous AIF is rate limiting for caspase-independent chromatin condensation induced by apoptotic stimuli (Cregan et al, 2002;Gallego et al, 2004;Kang et al, 2004;Cheung et al, 2005;Park et al, 2005).…”
Section: Aif Interactions With Nucleic Acids N Vahsen Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Microinjection of recombinant AIF is sufficient to induce hallmarks of apoptosis (chromatin condensation, rounding up of cells, phosphatidyl serine exposure) . Similarly, transfection of cells with an AIF mutant lacking the mitochondrial localization sequence in the N-terminus, misdirects AIF to the cytosol and to the nucleus, and results in cell killing (Loeffler et al, 2001). Recently, a chimeric protein containing an ErbB-2-specific antibody in the C-terminus and the cytotoxic moiety of AIF in the N-terminus has been shown to direct AIF to ErbB-2-expressing cancer cells, causing their demise (Yu et al, 2006).…”
Section: Chemotherapy and Mitochondriamentioning
confidence: 99%
“…1). Whereas AIF and Cyt c are considered the prototypic IMS proteins released upon MMP (due to microinjection experiments of recombinant molecules in intact cells, which demonstrated that either proteins suffice to induce the nuclear manifestations of apoptosis [61,62]), several other proteins are released from mitochondria upon OM permeabilization [63,64]. These include but are not limited to adenylate kinase [65], Smac/Diablo [63], Omi/HtrA2 [11,12], EndoG [17] as well as several pro-caspases [66].…”
Section: Detection Of Om Permeabilizationmentioning
confidence: 99%